Tantangan dan Solusi Pembelajaran Online Berbasis Digital pada Masa Pandemic Covid-19 - Muhammad Fadhil Al Hakim (UIN Imam Bonjol Padang, 2022)
Distance learning is one of the policies taken by the Indonesian government by studying it carefully as an effort to break the chain of the pandemic that is currently happening in the community, especially in the school environment. This policy is without social distancing that occurs in learning between teachers and students, which was originally a learning method mostly in the classroom meeting face to face, and now it is online-based learning. This writing uses the literacy study method, however, the implementation of online learning certainly has challenges/obstacles, both from the aspect of human resources, infrastructure, and technical implementation. With regard to this online learning policy, of course, all parties must understand well that online learning is an effective policy so that the learning outcomes of students during learning are not inferior to the results of face-to-face learning in the classroom as before the pandemic. Changes and developments in technology are very important for students in participating in online learning. Various platforms are used in online learning. Various positive responses were given by students regarding online learning. The competence and skills of teachers must be continuously updated and supported by school policies that encourage teachers to continue learning. Then it requires an evaluation related to online learning so that learning objectives can be achieved properly and maximally.